Designing Support Structures Post Sepsis in Children: Perspectives of the Queensland Paediatric Sepsis Program - Raman, Sainath; English, Alana; O'Keefe, Meagan; Harley, Amanda; Steele, Mary; Minogue, Jess; Weller, Kate; Long, Debbie; Irwin, Adam; Lister, Paula (Frontiers in Pediatrics, 2021)
Introduction: Paediatric post sepsis syndrome is poorly defined and causes physical, neurocognitive, psychosocial morbidity and family dysfunction. Families of sepsis survivors report unmet needs during care. Worldwide, the provision of post sepsis care is in its infancy with limited evidence to design clinical support pathways. Perspective: The Queensland Paediatric Sepsis Program (QPSP) developed a family support structure (FSS) to improve care during all stages of childhood sepsis. It was designed in partnership with consumers guided by information from consumers and it is partly delivered by consumers. Key areas include online, multimodal education for families and the ability to connect with other families affected by sepsis. The FSS is delivered by a multidisciplinary team (MDT) acting with clinicians local to the child. Families can join the FSS registry at any stage of their sepsis journey which connects them to our MDT team and opens opportunities to participate in future research and other initiatives. Improving public awareness is a critical outcome for our consumers and they have co-designed media and digital campaigns. Discussion The ideal FSS for post sepsis syndrome management is a clinical pathway designed in partnership with consumers of interventions proven to improve outcomes from sepsis that meets their requirements. The QPSP FSS is novel as it is co-designed with, and partly delivered by, consumers with interventions aimed to improve the entire spectrum of morbidities suffered by survivors and their families, not just physical sequelae. Evaluation is embedded in the program and outcomes will guide evolution of the FSS.